Design of a Sustainable Blockchain-Oriented Software for Building Workers Management - Pinna, Andrea; Baralla, Gavina; Lallai, Giorgia; Marchesi, Michele; Tonelli, Roberto (Frontiers in Blockchain, 2020)
The building workers sector is one of the most challenging for Human Resources (HR) management. In this work we propose a solution relying on the Blockchain technology and present the design of a Blockchain-Oriented Software system conceived for managing the building workers sector with a focus on workers' safety and guided by sustainable and Agile Methodologies in software design. The proposed approach takes advantage of different features of the Blockchain technology and provides transparency for labour inspectors, grants data integrity and immutability, relies in tamper proof time stamps for any recorded activity, allows the implementation of Smart Contracts where clauses are automatically respected without the need of a trusted control authority, acknowledges the legal requirements in the field, including the possibility of creating the Operational Safety Plans, which construction companies have to provide and finally implements the creation of vacant job positions which workers can find and apply to. In order to achieve these goals we adopt the Blockchain-Oriented Software Engineering (BOSE) methodology to design Blockchain software applications and apply an Agile methodology centered on Blockchain Software development, (called ABCDE) for the design and development of the decentralized application. Such methodology allows to center the software development around the actors of the system in the specific domain, such as Building Workers, Construction Companies, Labour Inspectors and so on. In addition we rely on the software sustainability analysis, based on the five dimensions of sustainability, to evaluate the approach and to avoid mistakes in the system development. We design system elements with specific diagrams and we divided our system in the on-chain and the out-of-chain components. The implementation of the system, done by using Ethereum and the ERC721 standard, allows us to improve some aspect of the design, to know the deployment and usage costs, and to evaluate the effect of the user interface. Finally, we discuss about the effects of our system and its sustainability, and provide a comparison of our system with a similar per aims but centralized system.